Pemanfaatan citra kamera inframerah thermal (kit) untuk mendeteksi area inflamasi pada tubuh manusia - Mardon Limena; Giner Maslebu; Ferdy Semuel Rondonuwu (Jurnal Teknosains, 2021)
Inflammation is an indication of an abnormality in the human body. Cases of inflammation occur accompanied by changes in temperature on the surface of the body. The location and location of the spread of inflammation cannot be seen solely by the human eye in detail. An imaging modality tool that is suitable for use in observing this problem is needed. In this study, the Thermal Infrared Camera (TIC) is used as an imaging modality. Samples in the form of a pair of legs in which one part of inflammation occurs are used as research objects. TIC is an imaging modality tool that can detect temperatures on the surface of an object quickly and is nondestructive. The results of the TIC image are processed using the global thresholding image processing method to distinguish between the inflammatory areas and normal areas more specifically. The results displayed indicate that there are differences in the image between the area of inflammation with the normal area of the patient's feet. The results of image processing data in the form of binary images show between the inflammatory area represented by white and vice versa the normal area represented by black. A comparison between the two conditions of the patient's feet before and after recovery shows the shrinkage of the area. There are two main results obtained in the exploration of this research, which is successful in distinguishing the inflammatory area from the normal area and the progress of recovery from the legs of the affected patient.